Wage Inequality in the United Kingdom, 1975-99 - Eswar S. Prasad (Institute for the Study of Labor (IZA), 2002)
This paper uses micro data from the New Earnings Survey to document that cross-sectional wage inequality in the U.K., which rose sharply in the 1980s and continued to rise moderately through the mid-1990s, has remained essentially unchanged in the latter half of the 1990s. As in the U.S., changes in within-group inequality are shown to account for a substantial fraction of the rise in wage dispersion that has occurred over the last 25 years. However, shifts in the structure of employment – including changes in the occupational and industrial composition of aggregate employment – are also shown to have had important effects on the evolution of wage inequality. In addition, there has been a significant convergence of the wage distributions for men and women; this has had a stabilizing effect on the overall wage distribution.
Keywords: E24; J31; 330; cross-sectional wage inequality; micro survey data; between- and within-group inequality; composition effects; Lohnstruktur; Großbritannien